Purification and preliminary characterization of latex proteases of Vasconcellea candicans (A. Gray) A. DC (Mito) - Gutiérrez, Ana I. F. (2017)
Preliminary studies indicate that, the "Mito" fresh latex, has a specific activity of papain from 1.84 times greater than that found in the latex of papaya, so the objective of this study was to purify and characterize "Mito" fresh latex proteases that have activity of papain. The crude extract protease was obtained from the "Mito" latex which was re-suspended (1:1) in 10 mM Na acetate buffer at pH 5.0; immediately proteins were precipitated at pH 9.0 and then with 45% ammonium sulfate. Subsequently, the proteins were purified on a Sephadex G-100 column and were three fractions: A, B and C. Using as a substrate casein, the enzymatic specific activity (ESA) was measured and was found to be the fraction A was 87.74 nkat.mg-1protein, for fraction B was 14.93 nkat.mg-1protein and for fraction C it was 16.13 nkat.mg-1protein. ESA of fraction A against papain of fresh latex of C. papaya was 13.3 times greater. Electrophoretic analysis (12% denaturant gel) shows for A fraction, two protein bands having one of them a relation similar to the papain standard. In addition, there was observed that the A fraction (papain of "Mito") against different concentrations of casein, used as a substrate, displays a michaeliane sigmoid curve; different volumes of enzyme shows a linear behavior; it has an optimum pH of 7.5 and is active up to 60 °C.